A Review of Hadith Concerning the Characteristics of Ya’juj Ma'juj and its Relevance to Life in Contemporary Society: Tinjauan Hadits tentang Karakteristik Ya’juj Ma’juj dan Relevansinya terhadap Kehidupan Masyarakat Kontemporer - Fuad Jasir; Aisyah Simamora; Nurliana (Jurnal Living Hadis, 2024)
Gog and Magog are often the subject of speculation and give rise to various interpretations among scholars and the Muslim community. As a creature mentioned in the Qur'an and Hadith, the Gogg and Magog entity is necessary. However, an explanation of who they are, how they appear, and their traits that tend to be destructive still requires further research based on authentic Hadith. There are also quite a few who interpret Gogg and Magog as an attribute, not an attribute. Therefore, this research aims to determine the physical identification and characteristics of Gog and Magog through a review of the Hadith. The method used in this research is library research using a content analysis approach. The research results show that Gog and Magog have striking physical characteristics such as wide faces, small eyes, curly hair, and short bodies. Apart from that, they are also described as beings who are destructive, know no mercy, and cause great damage to the earth. This research emphasizes the importance of an in-depth understanding of related hadiths to provide further insight into the role and impact of Gog and Magog in the context of Islamic eschatology so that society can be more aware of social issues.